2005
DOI: 10.1021/bi050906n
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Human Histone H3 Variants during Mitosis

Abstract: Phosphorylation of histone H3 is a hallmark event in mitosis and is associated with chromosome condensation. Here, we use a combination of immobilized metal affinity chromatography and tandem mass spectrometry to characterize post-translational modifications associated with phosphorylation on the N-terminal tails of histone H3 variants purified from mitotically arrested HeLa cells. Modifications observed in vivo on lysine residues adjacent to phosphorylated Ser and Thr provide support for the existence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 55 publications
5
57
0
2
Order By: Relevance
“…The bulkiness of K4 methylation likely compromises H3 tail interactions with the narrow substrate-binding groove of haspin. This finding is consistent with the observation that H3T3ph was detected adjacent to H3K4me, but not to H3K4me2 or H3K4me3, among histone peptides from mitotic cells (26). In mitosis, H3K4me2, H3K4me3, and H3T3ph have distinct localizations at centromeres (7,27).…”
Section: Discussionsupporting
confidence: 91%
“…The bulkiness of K4 methylation likely compromises H3 tail interactions with the narrow substrate-binding groove of haspin. This finding is consistent with the observation that H3T3ph was detected adjacent to H3K4me, but not to H3K4me2 or H3K4me3, among histone peptides from mitotic cells (26). In mitosis, H3K4me2, H3K4me3, and H3T3ph have distinct localizations at centromeres (7,27).…”
Section: Discussionsupporting
confidence: 91%
“…Mass spectrometry analyses of human histone H3 during mitosis revealed that phosphorylation and methylation can be found on adjacent residues of the same H3 molecule such as Lys9/Ser10 and Lys27/Ser28, 11,12 providing support for the "methylation/phosphorylation" binary switch hypothesis. 26 This hypothesis proposed that post-translational modifications on adjacent amino acids, such as methylation of Lys9 and phosphorylation of Ser10 on histone H3, could modulate the binding of effector molecules to histones.…”
Section: Histone H3 Phosphorylation During Mitosismentioning
confidence: 90%
“…4,8,10 In mammalian cells, histone H3 is phosphorylated at several sites during mitosis, including serines 10 and 28 (H3S10ph and H3S28ph) and threonines 3 and 11 (H3T3ph and H3T11ph). 8,[11][12][13] The mitotic phosphorylation of at least some of these residues is conserved in a variety of metazoa, fungi, plants and protozoa. [8][9][10][11] Moreover, several kinases implicated in phosphorylating histone H3 during mitosis in mammalian cells, Aurora B for H3S10 and H3S28 and Haspin for H3T3, 2,8,14 appear to have orthologs in a wide spectrum of eukaryotes (Fig.…”
Section: Histone H3 Phosphorylation During Mitosismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the availability of an array of techniques for the elucidation of post-translational modifications [4][5][6], their study continues to present a formidable analytical challenge. Mass spectrometry (MS) is playing an increasingly important role in such analyses because it provides a fast, sensitive means to specifically localize and characterize covalent modifications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%